Disseminated Kaposi sarcoma patients exhibit an expanded population of CD8+CD57+ T cells and an immunosenescence profile - Flores-Gonzalez, Julio; Ramón-Luing, Lucero A.; Islas-Muñoz, Beda; Volkow-Fernández, Patricia; Chavez-Galan, Leslie (Frontiers in Immunology, 2025)
IntroductionKaposi’s sarcoma herpesvirus (KSHV) remains the most common opportunistic malignancy that contributes to morbidity and mortality among persons living with HIV (PLWH) worldwide. The immune response in PLWH can exhibit signs of functional exhaustion, characterized by CD57 expression and mitochondrial dysfunction in T-cells. Valganciclovir (VGC), as an add-on therapy in patients with disseminated Kaposi Sarcoma/human immunodeficiency virus (DKS/HIV), modulates the activation of T-cell subsets; however, its effect on the T-cell immunosenescence profile is unclear.MethodsThis study evaluated the T-cell immunosenescence profile in DKS/HIV patients who received two treatment schedules: A group received antiretroviral therapy (cART) as conventional therapy (CT, n=10), while a second group received an experimental regimen, consisting of VGC initially plus cART (VGC+cART, n=10) by the fourth week. Mononuclear cells from DKS/HIV patients were obtained at baseline (W0) and at weeks W4 and W12 of treatment. T-cells were labeled with cell markers such as CD3, CD4, CD8, CD27, CD57, KLRG1, PD-1, TIM-3, and GLUT1, as well as soluble molecules and a proteome profile array of proteins related to proteases.ResultsData showed that DKS/HIV patients have an increased frequency of GLUT1+ T-cells at diagnosis, which was not modified after treatment initiation. The presence of CD8+CD57+KLRG1+ T-cells was expanded in DKS/HIV patients and maintained across follow-up once VGC+cART treatment was started. Although DKS/HIV patients display high plasma levels of soluble ligands for KLRG1 (E-cadherin) and TIM-3 (Gal-9) at diagnosis, together with proteases associated with the regulation of T-cells and the induction of T-cell immunosenescence, both treatment schedules reduce their soluble levels after 12 weeks of follow-up.DiscussionThe microenvironment generated in DKS/HIV patients increases the frequency of T-cells exhibiting an immunosenescence phenotype, and this effect is independent of the treatment schedule used, suggesting that during coinfection, a chronic immunosuppressive microenvironment may develop, impairing immune surveillance and resilience. These results could be explored to identify novel therapeutic approaches.